World Dance Day: A Cultural Conservation in Maintaining Local Wisdom of Traditional Arts - Rosmiati, Ana; Supriyanto, Supriyanto; Budiwiyanto, Joko; Mulyadi, Tubagus (Institut Seni Indonesia Surakarta, 2022)
The research entitled